Institutional transformation towards Open Science: Experiences from UiT The Arctic University of Norway - Ruud, Kenneth (Septentrio Conference Series, 2017)
Watch the VIDEO here. Opening speech by Kenneth Ruud, prorector of research at UiT The Arctic University of Norway.